(untitled) (Research, Society and Development, 2022)
Brazil’s Olympic participation in the 50-metre freestyle since the first Olympics in which this modality was introduced in 1988 until the last Tokyo 2020 Olympics can bring evidence that will help guide the understanding of the sports participation of Brazilian athletes in this modality. There are several aspects that can interfere with the performance of athletes, such as: Physical, technical, tactical and emotional aspects. Therefore, it is important to investigate the consistency of Brazilian performance in this modality. This work aimed to critically discuss the sporting performance of Brazilian athletes in 50-meter freestyle events. This study adopts a quantitative approach with descriptive analysis applied in order to observe a phenomenon and the conditions, facts and variables that contributed to the events that were related to the proposed fact. The data were obtained through the website: “https://olympics.com/olympic-games”, with information provided by the International Olympic Committee (IOC). Among the fifteen best times, of the four times that the Brazilians climbed to the podium, three times are among the best, one of which is in the Top-3 of best times in the history of this modality in particular, which shows consistency in the performance data of the Brazilian athletes. In a scenario of accentuated inequality, sport presents itself as a mechanism of social inclusion, and that despite the adversities, Brazilian athletes have demonstrated consistency in Olympic results throughout the trajectory of this modality.